Developing a consequence management assessment framework. (31st May 2019) - McDonald, Kenneth; Prins, Robert
This research developed an assessment process framework and tool to assess national consequence management capacity. The research applied a value focused thinking and the Systems Design Process (SDP) to create a framework that effectively analyses a nation's capacity to handle extreme crisis situations to include Chemical, Biological, Radiological, Nuclear and Explosive (CBRNE) events. The research conducted extensive stakeholder analysis to identify critical metrics in identifying a nation's capacity and capabilities. Weighting and scoring of the value metrics was applied to develop scoring assessments. The results provided a usable assessment model that tracks capacity progress over time. The model provides a value contribution to the development of an effective assessment tool and achieves the goal of providing a practical tool for assessment. This research takes assessing a very difficult and complex system and makes it relatively easy and simple, while providing solid evidence of capacity improvement or deterioration over time.